Exploring perspective of impact ranking university trend in five universities in East Java Indonesia - Fasih Bintang Ilhami; Mufidatul Khasanah; Nadi Suprapto; Bambang Sigit Widodo (Social Sciences and Humanities Open)
Global university ranking systems play a crucial role by providing the foundation for competition, as exemplified by the Times Higher Education (THE) rankings. The indicators are designed to offer a clear understanding of the teaching and learning environment. This study aims to explore the trends in university impact rankings by THE, achieved by universities in East Java, Indonesia. This study uses a minireview methodology from THE website. The findings indicate that teaching, research environment, and research quality are the three indicators that hold significant weight in the university impact rankings across five universities in East Java year after year by THE ranking.